2019
DOI: 10.15171/jcvtr.2019.40
|View full text |Cite
|
Sign up to set email alerts
|

Congestive heart failure is the leading cause of pleural effusion in the north-west of Iran

Abstract: Introduction: Pleural effusion (PE) is a common manifestation of pulmonary and non–pulmonary diseases, and the first step for diagnosing the etiology is analysis of pleural fluid. The aim of this study was to determine the epidemiology of PE in a tertiary referral hospital in the North-West of Iran. Methods: All patients with PE who referred to the department of pulmonary diseases in tertiary centre of Tabriz University of Medical Sciences between 2015 and 2016 were enrolled. Complete enumeration method used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Worldwide, the leading causes for pleural effusions are cardiac failure, malignancy and infections 22–27 . However, the aetiology might differ depending on the geography and the pattern and prevalence of disease burden in the local population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, the leading causes for pleural effusions are cardiac failure, malignancy and infections 22–27 . However, the aetiology might differ depending on the geography and the pattern and prevalence of disease burden in the local population.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the leading causes for pleural effusions are cardiac failure, malignancy and infections. [22][23][24][25][26][27] However, the aetiology might differ depending on the geography and the pattern and prevalence of disease burden in the local population. For example, in the Indian subcontinent and in African nations, the most common cause for pleural effusion is tuberculosis, understandably due to higher prevalence of tuberculosis in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnea is a subjective suffering of breathing difficulty. It affects up to 80% of patients with malignant pleural effusion [1][2][3] and a greater percentage of those with heart failure-associated effusions [4]. It was found that pleural effusions can have a large effect, on breathing, quality of life [5], sleep [6], and exercise capacity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil dari penelitian menunjukkan bahwa sesak napas adalah keluhan yang paling sering dirasakan oleh pasien yang mengalami gagal jantung, pasien gagal jantung mengalami kesulitan bernapas, napas cepat dan dangkal [20]. Sesak napas yang dirasakan oleh pasien CHF dapat disebabkan karena adanya efusi pleura, CHF merupakan penyebab paling umum pada efusi pleura [27], hasil penelitian yang dilakukan di Iran juga menyebutkan bahwa CHF merupakan penyebab paling umum terjadinya efusi pleura [22] Efusi pleura efusi pleura adalah akumulasi cairan yang tidak biasa di rongga pleura, biasanya disebabkan oleh berkurangnya penyerapan limfatik atau kelebihan cairan, akibatnya kapasitas paru akan berkurang [13]. Efusi pleura diakibatkan karena adanya peningkatan tekanan vena sistemik dan tekanan kapiler paru [11], ketika terjadi peningkatan pada kapiler paru, terdapat peningkatan jumlah cairan yang masuk pada ruang interstisial paru yang menyebabkan adanya peningkatan tekanan, selain itu penurunan curah jantung yang disebabkan oleh kegagalan kontraksi jantung juga membuat aliran oksigen ke jaringan tubuh menjadi berkurang, hal inilah yang juga dapat menyebabkan tubuh mengalami desaturasi yang ditandai dengan menurunnya tingkat saturasi oksigen dalam tubuh dan timbul sesak sebagai respon tubuh [20].…”
unclassified